Effects of (+)-bicuculline, a GABAa receptor antagonist, on auditory steady state response in free-moving rats. - Mayako Yamazaki; Sokichi Honda; Keisuke Tamaki; Megumi Irie; Takuma Mihara (PLoS ONE, 2020)
Auditory steady-state responses (ASSRs) are states in which the electrical activity of the brain reacts steadily to repeated auditory stimuli. They are known to be useful for testing the functional integrity of neural circuits in the cortex, as well as for their capacity to generate synchronous activity in both human and animal models. Furthermore, abnormal gamma oscillations on ASSR are typically observed in patients with schizophrenia (SZ). Changes in neural synchrony may reflect aberrations in cortical gamma-aminobutyric acid (GABA) neurotransmission. However, GABA's impact and effects related to ASSR are still unclear. Here, we examined the effect of a GABAa receptor antagonist, (+)-bicuculline, on ASSR in free-moving rats. (+)-Bicuculline (1, 2 and 4 mg/kg, sc) markedly and dose-dependently reduced ASSR signals, consistent with current hypotheses. In particular, (+)-bicuculline significantly reduced event-related spectral perturbations (ERSPs) at 2 and 4 mg/kg between 10 and 30 minutes post-dose. Further, bicuculline (2 and 4 mg/kg) significantly and dose-dependently increased baseline gamma power. Furthermore, the occurrence of convulsions was consistent with the drug's pharmacokinetics. For example, high doses of (+)-bicuculline such as those greater than 880 ng/g in the brain induced convulsion. Additionally, time-dependent changes in ERSP with (+)-bicuculline were observed in accordance with drug concentration. This study partially unraveled the contribution of GABAa receptor signals to the generation of ASSR.